2014
DOI: 10.1093/jpepsy/jsu020
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Child Sleep From Parent Report of Time in Bed: Development and Evaluation of Adjustment Approaches

Abstract: Simple adjustment factors can enhance the correspondence and utility of parent reports of child sleep duration for clinical and research purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 25 publications
1
20
1
Order By: Relevance
“…Our finding that parents overestimate their toddlers’ sleep by over 38 minutes compared to actigraph records is slightly longer than reports of other researchers from studies of older children (Nelson et al, 2014; Dayyat et al, 2011; Warner, Molinari, Guyer & Jenni, 2008). That there are differences in bedtime reports and sleep onset times should not be surprising because parents are not typically asked when their child fell asleep, only when the child was put to bed.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Our finding that parents overestimate their toddlers’ sleep by over 38 minutes compared to actigraph records is slightly longer than reports of other researchers from studies of older children (Nelson et al, 2014; Dayyat et al, 2011; Warner, Molinari, Guyer & Jenni, 2008). That there are differences in bedtime reports and sleep onset times should not be surprising because parents are not typically asked when their child fell asleep, only when the child was put to bed.…”
Section: Discussioncontrasting
confidence: 71%
“…We investigated discrepancies between parent diary reports and actigraph records for four sleep characteristics – diary reports of bedtime compared to actigraph records of sleep onset, diary reports of wake time compared to actigraph records of sleep offset, total nighttime sleep (parent-reported bedtime to wake time compared to actigraph recorded sleep onset to offset) and total sleep time (total nighttime sleep plus parent-reported and actigraph recorded nap sleep). Based on previous findings of discrepancies between parent sleep diary reports and actigraph recordings in young children (Acebo et al, 2005; Dayyat et al, 2011; Nelson et al, 2014), we expected differences between parent reports and actigraph records for all four measures of sleep characteristics in toddlers.…”
Section: Toddler Sleepmentioning
confidence: 91%
See 1 more Smart Citation
“…However, given that pediatricians generally make recommendations based on a parent’s report of children’s sleep duration rather than directly measured sleep duration, our sleep duration measurement is consistent with pediatric practice. Though parent- reported sleep duration of children consistently overestimates actigraphy-measured sleep duration by about half an hour per night(32,33), the correlation of parent-perceived sleep duration and actigraphy-measured sleep duration is high among 4–9-year-old children(3234), with parents of older children within this age range making more accurate reports of their children’s sleep(32). Thus, because shorter parent-perceived sleep duration translates to shorter actual sleep duration, this discrepancy is not especially problematic for our study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, adults in Australia 17 and the US 25 showed an association between obesity and short/long sleep duration. Additionally, studies of young Swedish women 11 , a community prospective cohort study in Zurich 26 , Brazilian adults 27 , and a populationbased study in the US 28 showed that obesity was associated with short sleep duration. The Insulin Resistance Atherosclerosis Study…”
Section: Discussionmentioning
confidence: 99%